Overview of Novel Antipsychotic Drugs: State of the Art, New Mechanisms, and Clinical Aspects of Promising Compounds - Letizia Biso; Marco Carli; Marco Scarselli; Biancamaria Longoni (Biomedicines)
Antipsychotic medications are a vast class of drugs used for the treatment of psychotic disorders such as schizophrenia. Although numerous compounds have been developed since their introduction in the 1950s, several patients do not adequately respond to current treatments, or they develop adverse reactions that cause treatment discontinuation. Moreover, in the past few decades, discoveries in the pathophysiology of psychotic disorders have opened the way for experimenting with novel compounds that have alternative mechanisms of action, with some of them showing promising results in early trials. The scope of this review was to summarize the novel antipsychotics developed, their current experimental status, and their mechanisms of action. In particular, we analyzed the main classes of investigational antipsychotics, such as monoamine, glutamate, acetylcholine, cannabinoid receptor modulators, enzyme inhibitors, ion channel modulators, and mixed receptor modulators. In addition, the safety profiles and adverse effects of these drugs were carefully evaluated, considering the relevance of these aspects for patients’ drug adherence and quality of life, especially in the long-term treatment. Lastly, we tried to understand which compounds have greater potential to be approved by the principal drug regulatory agencies in the next years and if they could be used for diseases other than psychotic disorders.